Gambaran Tingkat Kemandirian Lansia Dalam Pemenuhan Aktivitas Sehari-Hari Di Desa Pinaling Kabupaten Minahasa Selatan - Sumarauw, Jeane L. I; Lolowang, Nolla Lisa; Mandagi, Natalia (Yayasan Syalom Cipta Sumikolah, 2024)
Independence in the elderly depends on their functional status in carrying out daily activities. Independence is an individual attitude that is acquired cumulatively in development where individuals will continue to learn to be independent in dealing with various situations in the environment, so that individuals are able to think and act on their own. The research used uses quantitative descriptive. This research aims to find out the description of the level of independence of the elderly in fulfilling daily activities in the work area of ​​the East Amurang Community Health Center, South Minahasa Regency. This data was collected using a questionnaire which was distributed directly to the elderly in Pinaling Village. The sampling technique used was purposive sampling with a total of 200 elderly respondents in Pinaling Village. The results of the research conducted showed that the majority of elderly people in Pinaling Village had a level of independence with 197 respondents (98.5%) of the 200 respondents studied, while respondents with a level of independence with the help of others were 3 respondents (1.5%). The conclusion from this research is that the majority of elderly people still have high levels of independence. Advice for the elderly is that they are expected to be active and participate in socialization and programs carried out by health services regarding independence in carrying out daily activities.